Methodical basis of formation of digital space performance of contractual construction works - Bondar, O.A.; Yesipenko, A.D.; Terentyev, О.О.; Verenich, O.V.; Petrenko, H.S. (Ways to Improve Construction Efficiency, 2021)
The article searches for an appropriate methodology for the formation of methodological and formal analytical basis for the modernization of models of construction organization based on BIM models. The leading area of application of BIM-technologies in construction is the transformation of disparate graphic and tabular elements from the design and estimate documentation into a single system of info-graphic graphic modules, which are integrated by a single information retrieval system. However, in the realities of the domestic construction market and construction administration systems, BIM technologies remain an aid to the visual-graphic and analytical presentation of the content of a construction development project as an object of construction and investment. However, the strategic trend of this market is the formation of construction development as a single environment of the construction project and as a format of construction administration. Given such strategic dominants, there is a need to redirect and readjust the functional content and graph-analytical design of VIM-technologies to the peculiarities of preparation and organization of the construction development project cycle (BDP) – from promoting the initial investment product idea to the end of the development contract. BIM-technologies should no longer be considered solely as an additional tool for visualizing the progress of the project cycle. It is substantiated that the digital space of the construction industry (construction projects, construction organizations-participants) in the development of information and communication technologies acquires the characteristics of an alternative construction business, which should function in a certain transformed environment of construction development projects. Technologies directly related to design and construction (BIM, augmented reality, laser scanning, etc.) increase the efficiency of investment and construction projects, while digital data analysis systems contribute to a better understanding of construction market trends.